Strumenti, tecniche e soluzioni Open Source a confronto per l'elaborazione fotogrammetrica delle immagini digitali in ambito archeologico - Montagnetti, Roberto; Chiraz, Pier Paolo; Ricci, Andrea; Pickel, David Gerald (Archeomatica, 2019)
This work wants to be an overview about the various "open source” software that can be used to obtain rendering and photogrammetric data geo-referenced from digital photos. In fact, all the phases of digital photogrammetric processing can be performed by open source software. This paper, therefore, wants to provide an alternative to the use of the most famous commercial photogrammetric software, taking into consideration and comparing the different methods of photogrammetric processing available in the open source environmental to obtain the final aims pursued and showing off how it is possible to integrate the information coming out the different software used in order to the best result possible. The software used were: MicMac, OpenMVG, CloudCompare, MeshLab, Qgis2.8 and GrassGIS7. The comparison between the different photogrammetric processings through the software mentioned above has been tested on a burial in "enchytrismòs” found out during the archaeological excavations in the site of Poggio Gramignano (Italy). Generally the main final results we can obtain from a photogrammetric survey are: • a 3d model of the area or og the object investigated in the form of a "dense points cloud” rendered with associated texture; • a Digital Surface Model (DSM); • an orthophoto. These results can also be geo-referenced in a geographic reference system and can be used for many different purposes in the light of the kind of the research carring out. Even in this case, therefore, we worked on reaching the same final results that the "open source” software used allowed to obtain, resulting in a very hight reliability. Moreover, the final outputs can be managed and used to obtain, in the GIS environment, further data such as sections, altimetric profiles and so on and to associate them a database in order to have alphanumeric information for every vectorial element.